ABNORMAL UTERINE BLEEDING AS A RELEVANT PROBLEM IN MODERN GYNECOLOGY (World Bulletin of Public Health, 2026)
Abnormal uterine bleeding (AUB) remains a major clinical challenge in modern gynecology due to its high prevalence, etiological heterogeneity, and significant impact on women’s health and quality of life. This review summarizes current approaches to the classification and pathogenesis of AUB, with emphasis on the FIGO PALM–COEIN system and the evolution of standardized terminology. Epidemiological features of AUB are analyzed with consideration of age-related differences between reproductive-aged and perimenopausal women, as well as methodological factors contributing to variability in prevalence estimates. Particular attention is paid to nonstructural forms of AUB, including ovulatory and endometrial dysfunction, local disturbances of hemostasis, angiogenesis, hormonal imbalance, and impaired endometrial repair. The review highlights the high rate of disease recurrence and the limitations of symptom-oriented and morphology-based management strategies. Current evidence supports the need to expand the clinical paradigm of AUB beyond structural causes and acute bleeding control toward a more comprehensive, pathogenetically oriented and individualized approach to diagnosis and treatment.
Keywords: abnormal uterine bleeding; PALM–COEIN classification; endometrial dysfunction